The importance of entrepreneurship and innovativeness for the economic development of the Republic of Serbia - Šormaz Goran (Trendovi u Poslovanju)
The economic development of a country is impossible without innovation and entrepreneurship. As privately owned economic entities are one of the main drivers of the economy, job creation, as well as the growth of production and consumption, can be said that innovations, with the help of entrepreneurship, drive the national and world economy. Innovation is a crucial element of entrepreneurship, so companies must continuously innovate their business in order to avoid stagnation and possible closure. The causal links between innovation, entrepreneurship and economic development should be carefully analyzed and monitored, taking into account all the circumstances at a given time. Based on such an analysis, it is possible to identify the reasons for the stagnation and decline in their correlation, in order to react more promptly in the future. Inventiveness is the most valuable resource of any company, so it is very important to encourage creative thinking and presenting new ideas. Innovations have a direct impact on increasing productivity and increasing competitiveness, and continuous business innovation implies constant adjustment and the ability to cope in a competitive market. Innovation and entrepreneurship are key to the economic development of any country, as they provide numerous opportunities and variations, applicable in every economic system.